1992
DOI: 10.1159/000186806
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hyperlipidemia with Probucol Suppresses the Development of Focal and Segmental Glomerulosclerosis in Chronic Aminonucleoside Nephrosis

Abstract: We have recently reported that a lipid-lowering agent, probucol, reduces proteinuria in puromycin aminonucleoside (PA)-induced nephrotic rats (PAN). In this study, we examined whether a long-term treatment of hyperlipidemia with probucol can suppress the development of focal and segmental glomerulosclerosis (FSGS) in chronic PAN. A chronic PAN model was made with repeated intraperitoneal injections of PA (initially 100 mg/kg body weight followed by 25 mg/kg 5 times at 2-week intervals). Two weeks after the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…They concluded that probucol rendered LDL cholesterol resistant to oxidative modification as shown in a previous study [36]. Similarly, progressive renal injury by chronic puromycin aminonucleoside nephrosis was inhibited by probucol treatment [9,40]. On the other hand, the drug failed to prevent increasing fibrosis in the acute model by puromycin aminonucleoside [41], while the combination of probucol and vitamin E treatment attenuated interstitial inflammation [42].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…They concluded that probucol rendered LDL cholesterol resistant to oxidative modification as shown in a previous study [36]. Similarly, progressive renal injury by chronic puromycin aminonucleoside nephrosis was inhibited by probucol treatment [9,40]. On the other hand, the drug failed to prevent increasing fibrosis in the acute model by puromycin aminonucleoside [41], while the combination of probucol and vitamin E treatment attenuated interstitial inflammation [42].…”
Section: Discussionmentioning
confidence: 87%
“…Treatment by antilipemic agents has been shown to ameliorate renal injury in hyperlipidemic animals. The effects seem to be brought about partly by the lipid-lowering action of the drugs used in each study, because the serum Nakao/Nosaka/Imaki/Noiri/Toda/Doi/ Suzuki/Fujita/Kimura cholesterol levels of experimental animals are reduced to some extent by the treatment [6,7,9,34,35]. However, probucol, a lipid-lowering agent, has also been reported to have an antioxidant effect, which was clearly shown in the experiment by Kita et al [36] using the Watanabe hereditable hyperlipidemic rabbit model to ameliorate atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No doubt, the same agent could be used to explore the situation in glomerulonephritides. Probucol is an effective antioxidant that is used in man [57], and we know that it can stop develop ment of focal glomerulosclerosis [58],…”
Section: Glom Erulonephritis and G Lom Erulosclerosismentioning
confidence: 99%
“…Probucol is an anti-oxidant that also lowers the blood lipids. Probucol suppresses focal glomerulosclerosis [58,98] …”
Section: Wardlementioning
confidence: 99%